Overview of the frontal sinus anteroposterior size based on against lateral cephalometric radiographs chronological age as forensic identification - Marsya, Georgiana; Sasmita, Inne Suherna; Oscandar, Fahmi (Padjadjaran Journal of Dentistry, 2017)
Introduction: One part of the most important individual identification procedure is approximate age can be done on an individual living or dead. Judging from some of the methods that have been there, have not found a method forecasts age through the frontal sinuses, particularly research conducted in Indonesia. The frontal sinus can be used for identification because the frontal sinuses began to evolve and look at radiographs at the age of 7 years and did not change after the age of 20 years, it reveals the existence of differences in the size of the frontal sinuses with age. Objective: To asses of the frontal sinus anteroposterior size based on against lateral cephalometric radiographs chronological age as forensic identification. Methods: A number of samples are 502 lateral cephalometric patient data from secondary data of patients aged 7-20 years, 335 pieces of lateral cephalometric. Purpose of of the study was to asses the frontal sinus anteroposterior size chronological age as forensic identification. Radiograph female patients and 167 pieces in male patients. Data anteroposterior size of the frontal sinus is obtained by pulling the longest line perpendicular to the line of Sh-Sl. Results: The results showed that at the age of 7 years the average size of the frontal sinus anteroposterior 4.20 mm and 5.05 mm which is the smallest size, while the average size of the biggest, by 8.46 mm in women and men at the age of 11.37 mm 20 years. Conclusions: In women, the fastest increase occurred at the age of 7-8 years, males at the age of 16-18 years. The frontal sinuses anteroposterior size increases with age, both men and women.